Determination of the Vitality of Pollen Grains in Arganica Thapsia Plant in the Green Mountain Region, Libya - Shoaib , Ezzedine; Batu, Miftah Abdulqader (Al-Mukhtar Journal of Sciences, 2014)
Derias plant Thapsia garganica is an endemic wild plant species in many parts of El-jabal Al-khder region, northeast of Libya. The aim of this research was togather information about the pollen grains viability in Thapsiagarganicain three different locations. The results of the present study illustrated those pollen grains of this plant showed different percentages in pollen viability regarding to the statistical analysis. The three locations in El-jabal Al-khder region showed significant differences in the pollen grains viability.The results showed Alabraq location was the highest value of the pollen grains viability 72.67%, while 61.40 %, 54.26% in Belgaray and Alqubba locations respectively. The high viability of pollen grains recorded during the first week ,then decrease in the second and third week in all studied locations.